Secular cultural policy in Islamic countries: desirability and feasibility. Issue 1 (2nd January 2017) - Mehregan, Abbas
Abstract : Secularism in Islamic countries is a hotly-debated topic which produces dramatic sociopolitical consequences on the one hand, and wide-ranging academic controversy on the other. The real social potential of secularism among Muslim populations is an issue that is not always estimated properly. The present paper first reviews some historical examples of secular cultural policy in Islamic countries. This review covers the secular reforms in four political, social, legal, and educational spheres. Subsequently, using data from the World Values Survey, it compares empirically the desirability of a public role for religion in 18 Islamic and Western countries. Furthermore, it examines the acceptability of Western secular culture in six countries in the Muslim world. Bearing in mind Casanova's analytical approach to the theory of secularization, it comes to the conclusion that a democratic application of a secular cultural policy in Islamic countries is neither desirable nor feasible.